KAJIAN PENDAHULUAN SISTEM PEMANFAATAN AIR HUJAN - Indriatmoko, Robertus Haryoto; Rahardjo, Nugro (Jurnal Air Indonesia, 2015)
Rainwater is an abundant source of water, especially during the rainy season. But otherwise if it is not managed properly, it can lead to disasters, such as floods or landslides. Therefore it is very important to harness rainwater by doing the best way, ie by the rain harvesting and then infiltrating the water back into the ground. Many countries have shown good results in the use of rainwater for various purposes. Dominican Republic, Singapore, Japan, China, Thailand and Indonesia are 7 countries which have a lot of implementing rainwater utilization system very well. Rainwater can be used as a source of clean water to meet the drinking water needs. Artificial recharge for rain water lets the water goes to infiltrate back into the soil is a powerful effort to maintain and preserve the ground water potential. Besides, infiltration of rainwater into the soil also can prevent land subsidence. Because of the importance of rainwater management system, it should be included in the educational curriculum both for elementary to upper secondary level. Similarly, the obligation for proper implementation must also be supported by adequate rules or regulations.Ã‚Â Keywords : Rainwater management, artificial recharge.